Case reportIntradural chordoma mimicking a lateral sphenoid wing meningioma: a case report - Kunert, Przemysław; Dziedzic, Tomasz; Matyja, Ewa; Marchel, Andrzej (Folia Neuropathologica, 2012)
Chordomas are rare tumours arising from notochordal remnants. Classical chordomas are generally extradural and, despite benign histopathology, they typically destroy the clivus and surrounding bone structures. Intradural lesions are extremely rare and less than thirty cases of intracranial, exclusively intradural chordomas have been reported so far. The intracranial, intradural but extranotochordal location of chordoma is extremely unique. The authors present a case of chordoma in intracranial location that clinically mimics lateral sphenoid wing meningioma. A previously healthy 39-year-old man was admitted to our Department because of optic disc oedema without neurological deficits. Neuroimaging studies showed a large, contrast-enhanced tumour in the right frontotemporal region that was thought to be a pterional meningioma. The patient underwent successful removal of the tumour. Histopathological study revealed a typical pattern of chordoma, confirmed by immunohistochemical findings. Because of the tumour location the differentiation between chordoma and chordoid meningioma ought to be considered. Such cases, including the present one, may lead to the conclusion that embryonic notochordal remnants may be lost in different places, even away from the neuroaxis.